MENGEKSPLORASI OLAHRAGA PERMAINAN TRADISIONAL PERESEAN (STUDI KASUSU PERMAINAN TRADISIONAL PERESEAN DI DESA MARONG) - Ashari, Lalu Hasan; Muzakir, Muzakir (LPPM Institut Pendidikan Nusantara Global, 2020)
Traditional game sports are the result of human creativity, taste, and initiative. Traditional game sports have now experienced a shift, one of it is the shift in a traditional sports games for the Lombok Sasak community. By doing this research, it is hoped that researchers will be able to explore traditional game sports and the meaning of exploring traditional sports games research for the community. This study uses a qualitative research method of phenomenology. The research location is in Marong Village, East Praya District, Central Lombok Regency. The subjects of this research are the people in Marong Village, this research was using snowball sampling technique (snowball). Collected through in-depth interviews and observations. The results of this research indicate that. Peresean traditional game sport is a traditional sport of the Sasak people who fights two men (pepadu) using weapons from rattan sticks and shields. In the traditional peresean games, there are rules and sanctionsthat their implementation. Currently, peresean performances are carried out at certain times, such as village or district birthdays, wedding events, in famine seasons, the anniversary of the Independence Day of the Republic of Indonesia, or in welcoming guests. The values that ​​contained in the peresean traditional game sports are values ​​about life such as the value of respecting brotherhood, friendship, economy, kinship, belief, culture and artistic values. Male valor, martial arts, sportsmanship spirit, self-respect and friendship. So the performance of the traditional game of Peresean in the Sasak people of Lombok has experienced a shift both in terms of rules, meaning and timing of implementation.